2017
DOI: 10.1007/s12192-017-0762-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of sHsps in organizing cytosolic protein aggregation and disaggregation

Abstract: Small heat shock proteins (sHsps) exhibit an ATPindependent chaperone activity to prevent the aggregation of misfolded proteins in vitro. The seemingly conflicting presence of sHsps in insoluble protein aggregates in cells obstructs a precise definition of sHsp function in proteostasis networks. Recent findings specify sHsp activities in protein quality control systems. The sHsps of yeast, Hsp42 and Hsp26, interact with early unfolding intermediates of substrates, keeping them in a ready-to-refold conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 77 publications
(149 reference statements)
0
98
0
2
Order By: Relevance
“…During nucleation of aggregates, Mas5 would sequester clients, in reparable stages of unfolding, probably preserving a native-like central structure; insertion of Mas5 moieties between the misfolded substrates would keep them apart, preventing an irreversible aggregation state ( Figure 7E). A role similar to this one has been proposed at extreme temperatures for the budding yeast chaperone Hsp42, with an N-terminal prion-like domain holding the chaperone's aggregase activity (Mogk and Bukau, 2017;Specht et al, 2011). Once stress conditions would permit, disaggregases, such as Hsp104, would facilitate aggregate dissolution and protein refolding.…”
Section: Discussionmentioning
confidence: 80%
“…During nucleation of aggregates, Mas5 would sequester clients, in reparable stages of unfolding, probably preserving a native-like central structure; insertion of Mas5 moieties between the misfolded substrates would keep them apart, preventing an irreversible aggregation state ( Figure 7E). A role similar to this one has been proposed at extreme temperatures for the budding yeast chaperone Hsp42, with an N-terminal prion-like domain holding the chaperone's aggregase activity (Mogk and Bukau, 2017;Specht et al, 2011). Once stress conditions would permit, disaggregases, such as Hsp104, would facilitate aggregate dissolution and protein refolding.…”
Section: Discussionmentioning
confidence: 80%
“…It has been shown that the minimal region comprising only the ACD, and in some cases only the N‐terminal domain, are also capable of conferring protection during stressful conditions . It is now known that inside a cell, sHSPs function mainly by preventing the aggregation of nonnative, destabilized, denaturing and aggregation‐prone proteins during normal as well as stress conditions, thus acting as “stability sensors” of the proteome or by depositing along with the toxic aggregates of misfolded proteins within a confined location of the cell, hence functioning as “aggregases” . They also coordinate with the refolding and degradation machinery of the cell and contribute to proteostasis.…”
Section: Introductionmentioning
confidence: 99%
“…HSP60, HSP70, and HSP90 can bind to misfolded proteins to refold them. They can also neutralize the exposed hydrophobic regions in the misfolded proteins and stop their aggregation process [33]. In the CMA pathway, heat shock cognate protein 70 (HSC70) binds to the KFERQ motif of the misfolded protein and delivers it directly to a lysosome via LAMP2a for degradation ( Figure 1) [34].…”
mentioning
confidence: 99%